KAMPANYE KOMUNIKASI PEMASARAN DALAM MENINGKATKAN PERFORMA MEDIA DIGITAL JATENG POS SEBAGAI PUBLIC RELATIONS MANAGER DAN ADMINISTRATIVE MANAGER - Sekar Arum; S. Rouli Manalu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This fieldwork study examines the implementation of a marketing communication campaign designed to improve Jateng Pos’s digital media performance and strengthen its image as a media outlet close to Generation Z. The campaign was developed in response to low content reach, limited audience engagement, and the need to enhance Jateng Pos’s digital visibility. The campaign integrated the Integrated Marketing Communication (IMC) approach and Curated Flow Theory through several programs, including the Jangan Cuma Klik Judulnya campaign, Creative News Challenge, Jateng Pos Goes to School, media partnerships, and Instagram Ads. The author contributed to the campaign as the Public Relations Manager and Administrative Manager, with responsibilities including managing media relations, coordinating external partnerships, handling administrative documents, and overseeing financial administration. Based on the evaluation results, the campaign successfully improved Jateng Pos’s digital media performance by increasing audience reach, engagement, and information distribution. The campaign also contributed to strengthening Jateng Pos’s image and increasing brand awareness and brand activation among students in Central Java. These findings indicate that an integrated marketing communication strategy supported by multiple communication channels can effectively enhance digital media performance while building stronger relationships with the target audience.